Antimicrobial and antioxidant effect of lyophilized Fucus spiralis addition on gelatin film during refrigerated storage of mackerel. (January 2022) - Trigo, Marcos; Nozal, Pedro; Miranda, José M.; Aubourg, Santiago P.; Barros-Velázquez, Jorge
Abstract: Lyophilized alga Fucus spiralis powder was incorporated into a gelatin-based film and employed as a packaging system for mackerel ( Scomber scombrus ) muscle portions throughout a 9-day refrigerated storage period at 4 °C. In global terms, a progressive loss of quality could be observed in fish muscle with increasing storage time. Comparisons between batches allowed us to conclude an inhibitory effect of F. spiralis -containing films on microbial activity (assessment of aerobes, psychrotrophs, and proteolytic bacteria) and on lipid hydrolysis (as determined by free fatty acid formation) in mackerel muscle. The presence of the lyophilized macroalga in the packaging film also led to a higher retention of primary (peroxides) and secondary (thiobarbituric acid reactive substances) lipid oxidation compounds, while the formation of fluorescent compounds (interaction compounds between lipid oxidation compounds and nucleophilic molecules present in the fish muscle) decreased. Both antimicrobial and antioxidant effects were more intense when the concentration of alga in the packaging film was increased. The preservative effect resulting from the presence of F. spiralis in gelatin-based films demonstrates the potential employment of such bioactive films to improve the retention of fish quality and enhance its commercial value. Highlights: Lyophilized Fucus spiralis was incorporated into a gelatin packaging film. F. spiralis in the packaging film inhibited free fatty acid formation in mackerel. F. spiralis inhibited aerobes, psychrotrophs, and proteolytic bacteria in fish muscle. F. spiralis in the packaging film inhibited fluorescent compound formation. Superior retention of primary and secondary lipid oxidation compounds was observed.